Soil Amendment With Different Maize Biochars Improves Chickpea Growth Under Different Moisture Levels by Improving Symbiotic Performance With Mesorhizobium ciceri and Soil Biochemical Properties to Varying Degrees - Egamberdieva, Dilfuza; Li, Li; Ma, Hua; Wirth, Stephan; Bellingrath-Kimura, Sonoko Dorothea (Frontiers in Microbiology, 2019)
Chickpea (Cicer arietinum L.) is an important legume originating in the Mediterranean and the Middle East and is now cultivated in several varieties throughout the world due to its high protein and fiber content as well as its potential health benefits. However, production is drastically affected by prevalent water stress in most soybean-growing regions. This study investigates the potential of biochar to affect chickpea-Rhizobium symbiotic performance and soil biological activity in a pot experiment. Two different biochar types were produced from maize using different pyrolysis techniques, i.e., by heating at 600°C (MBC) and by batch-wise hydrothermal carbonization at 210°C (HTC), and used as soil amendments. The plant biomass, plant nutrient concentration, nodule numbers, leghemoglobin (Lb) content, soil enzyme activities, and nutrient contents of the grown chickpeas were examined. Our results indicated that plant root and shoot biomass, the acquisition of N, P, K, and Mg, soil nutrient contents, soil alkaline and acid phosphomonoesterases, and proteases were significantly increased by HTC char application in comparison to MBC char under both well-watered and drought conditions. Furthermore, the application of both biochar types caused an increase in nodule number by 52% in well-watered and drought conditions by improving the symbiotic performance of chickpea with Mesorhizobium ciceri. Rhizobial inoculation combined with HTC char showed a positive effect on soil FDA activity, proteases and alkaline phosphomonoesterases under well-watered and drought conditions compared to the control or MBC char-amended soils. This concept, whereby the type of producing biochar plays a central role in the effect of the biochar, conforms to the fact that there is a link between biochar chemical and physical properties and enhanced plant nutrient acquisition, symbiotic performance and stress tolerance.